Internship at “el recuerdo” child development center under the program my first steps from university of cordoba. (2020)
Cordoba “My first steps” in the modality of the internship has allowed trainee teachers to explore a real-life context working with young children from a vulnerable area in Monteria Cordoba, with the purpose of applying different strategies and practices that will help children in this program to get an initial encounter with the target language. Due to the difficulties of the current year and the inability of providing the face to face classes, the internship in the first semester 2020 has suffered some changes, and in order to continue the project, it was established to work in the designing of a unit plan and several lesson plans following some approaches that will be beneficial to this population of students. The objective of this paper is to describe my experience in this internship; designing some lesson plans for students at such a young age, as well as describing the activities carried out during the whole process of the internship. Following the designing of the lesson plans, this final report deals with the implementation of a play-based approach and the advantages of working with this one taking into account the children’s context and needs.